FAMILY AS A SOCIAL GROUP AND A SOCIAL INSTITUTION - Gaibova Nargiza Anorbaevna (American Journals Publishing, 2024)
Time goes on, the topic of families, for one reason or another, initially without a child, increasingly acquires, and is associated with the theoretical uncertainty of the scientific status of this type of family structure, as well as the applied significance of research in this area.
Keywords: Family, adolescent, sibling status, sibling relationship, conflict, eldest child, middle child, last child, only child, interpersonal relationships.